Potential and Characterization of Yeast from Soil Contaminated with Captan – Based Fungicide - Ratna Eka Sari Putri; Chosa Zahro Fatiha; Novia Dwi Putri (G-Tech: Jurnal Teknologi Terapan, 2025)
Captan is a fungicide that inhibits the growth of fungi such as Alternaria porri. This fungicide is non-systemic, forming a layer on the surface of leaves and fruit. The continuous use of captan fungicides can leave residues in the environment, especially in soil. One technique to reduce captan fungicide residues is bioremediation. Bioremediation is a way to remove fungicide residues by utilizing microorganisms. The purpose of the study was to obtain yeasts in land polluted with residues of fungicides made from active captan, knowing yeasts that are adaptive to various fungicide concentrations and have the potential to reduce the toxicity of fungicides made from active captan. This study includes soil sampling, isolation and characterization of yeasts morphologically and molecularly, yeast adaptation tests to fungicides, and degradation tests using a complete randomized design. In the adaptation test, all yeasts were able to grow on media added with various concentrations of fungicide product recommendations. Molecular identification of yeast includes DNA isolation, DNA amplification, PCR product sequencing, and molecular data analysis. In the treatment with the addition of yeast, the largest average diameter of A. porri on the seventh day of observation was in the treatment with the addition of W. anomalus and W. onychis yeast. The yeast with the highest ability to degrade fungicides containing the active ingredient captan is W. onychis.